MANAJEMEN PERUBAHAN - Wanuri, Wanuri (JURNAL STIE SEMARANG, 2011)
Change  management   is a science  and art to make changes  to the Planning  Organizing an effective  action  by distributing   the appropriate  human  resources  in managing  change.  Later in  the  implementation    of  changes  should   be  made  pengawan   tersbut  for   susuai   with  that planned  for  the achievement  of company  objectives. Leader  or  manager  must  be able  to provide   motivation   to  its staff  that  change  is a requirement   that must  be done  to change  a oraganisasi  can succeed.  J Harold  organizational change   approach   Leavit   stated   that   the  organization    can   be  changed   by  the  structure approach,  the approach  of technologies  and approaches  oranya. Leaders  must be able  to understand  the resistance  to individuals  in an organization   or company,  individual  resistance  include,  Habit  / Habitat,  Economic  Factors,  Safety  / Security, Worry About  Ketidakpastia  Apreori  Perception